Metastatic ovarian carcinoma in white-tailed deer (Odocoileus virginianus) from a conservation center in Medellín-Colombia - Duque-Arias, Santiago; Marín-Zapata, Alejandra; Restrepo-Rueda, Jakob; Úsuga-Monroy, Cristina; Llano, Horwald Alexander Bedoya (Brazilian Journal of Veterinary Pathology, 2025)
Wildlife animals in human care can develop pathological processes that rarely occur in their natural habitats, including neoplastic disorders. This report presents the post-mortem pathological findings of a white-tailed deer (Odocoileus virginianus) from a conservation center in Medellín, Colombia. O. virginianus had lung metastases originating from a primary papillary ovarian carcinoma. The post-mortem examination revealed macroscopic and microscopic involvement of multiple organs, including the ovaries, uterus, lungs, kidneys, liver, and spleen. Immunohistochemical analysis showed positive staining for pancytokeratin in neoplastic epithelial cells. This case underscores the importance of recognizing and understanding the multi-causal pathological processes contributing to the death of a wild animal in captivity.